The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0098795
|View full text |Cite
|
Sign up to set email alerts
|

Dissociative Part-Dependent Resting-State Activity in Dissociative Identity Disorder: A Controlled fMRI Perfusion Study

Abstract: BackgroundIn accordance with the Theory of Structural Dissociation of the Personality (TSDP), studies of dissociative identity disorder (DID) have documented that two prototypical dissociative subsystems of the personality, the “Emotional Part” (EP) and the “Apparently Normal Part” (ANP), have different biopsychosocial reactions to supraliminal and subliminal trauma-related cues and that these reactions cannot be mimicked by fantasy prone healthy controls nor by actors.MethodsArterial spin labeling perfusion M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
59
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 108 publications
(158 reference statements)
7
59
1
Order By: Relevance
“…Experiencing dissociation of self from the body might thus relate to failure to integrate complex somatosensory and vestibular cues (Blanke et al, 2002;Blanke and Arzy, 2005;De Ridder et al, 2007). In line with this idea, the involvement of the parietal regions has previously been indicated in functional neuroimaging studies in DID (Reinders et al, 2003(Reinders et al, , 2006Schlumpf et al, 2014) and depersonalization disorder (Simeon et al, 2000). Altogether, our findings along with previous reports suggest that the inferior parietal cortex plays a role in the neurobiology of dissociative and depersonalization symptoms in DID and PTSD.…”
Section: Discussionsupporting
confidence: 88%
“…Experiencing dissociation of self from the body might thus relate to failure to integrate complex somatosensory and vestibular cues (Blanke et al, 2002;Blanke and Arzy, 2005;De Ridder et al, 2007). In line with this idea, the involvement of the parietal regions has previously been indicated in functional neuroimaging studies in DID (Reinders et al, 2003(Reinders et al, , 2006Schlumpf et al, 2014) and depersonalization disorder (Simeon et al, 2000). Altogether, our findings along with previous reports suggest that the inferior parietal cortex plays a role in the neurobiology of dissociative and depersonalization symptoms in DID and PTSD.…”
Section: Discussionsupporting
confidence: 88%
“…2-30; [3], pp. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. This is a well-known problem in neuroscience and philosophy of mind, often referred to as the 'hard problem of consciousness'.…”
Section: Inferencementioning
confidence: 99%
“…In another study [23], doctors performed fMRI brain scans on both DID patients and actors simulating DID. The scans of the actual patients displayed clear and significant differences when compared to those of the actors.…”
Section: Inferencementioning
confidence: 99%
See 1 more Smart Citation
“…Pertinent clinical observations, evidence, explanations, and ways to deal with structural dissociation of the personality are presented in Van der Hart, Nijenhuis and Steele's book The Haunted Self (). Ground‐breaking controlled neuroimaging studies have demonstrated dissociative part‐dependent physiological and neurophysiological reactions to supraliminally and sublimally presented trauma‐related cues (Reinders et al ., ; Schlumpf et al ., ), as well as neurophysiological dissociative part‐dependent resting state differences (Schlumpf et al ., ).…”
mentioning
confidence: 97%